Pengembangan Media Virtual Laboratory Materi Virus untuk Meningkatkan Hasil Belajar Siswa - Yuli Wahyuni; Emilia Umrotin; Shidqi Hamdi Pratama Putera (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
One of the materials in biology subjects is Virus where the material is abstract so it is difficult to understand by students and often when carrying out practicum in the laboratory also the results of studying on viral material are still much too low less than KKM which is 75. The purpose of this development research is to develop a virtual media laboratory viral material as a learning medium that facilitates teachers and students in the learning process that is expected to improve student learning outcomes. This research uses a type of R&D research with 4D models consisting of Define, Design, Develop, Disseminate in its development procedures. This research was conducted at SMA SHafta Surabaya by grade 10 of 30 students. Virtual Media Laboratory consists of the design of learning media that will be developed in the form of story boards on Virus materials developed with Adobe Flash CS6 software. Based on the assessment of material experts, design experts, media experts in a row by 100% , 84.28%, 87.14% which is declared very valid means that new products can be used in the field for learning activities. The results of the field trial assessment of 98.33% are declared very valid meaning that new products can be used in the field for learning activities. There was an increase in students' learning outcomes which was known by comparing the pretest and postest results of 46 and 85. The average improvement of student learning outcomes is 2.6 with high media effectiveness. In conclusion, virtual media laboratory can improve the learning outcomes of grade 10 students of SMA Shafta Surabaya on virus material.